Oceanography from space (United States. National Aeronautics and Space Administration, 1986)
Folder with 13 posters; image on recto and descriptive text on verso. Gulf stream temperature; Western North Atlantic color; Sea-surface topography and ocean bathymetry; Winds over the Pacific; Seasonal Baja Ocean color; Tropical Pacific time series; 1982-83 El Niño; Spiral eddies; West coast upwelling; The marginal ice zone; Strait of Gibralter; Arctic pack-ice motion; Winds over the Atlantic and Indian Oceans.